Analysis of PMT Menu Budget Optimization in Posyandu Activities in Mimbaan Village Using The Simplex Method - Sukma Ayu Nur Aminah; Ida Fitriana Ambarsari; Lisma Dian Kartika Sari (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Mimbaan Village is one of the villages with the highest stunting rate  in Panji District. One way to prevent stunting is by providing Supplementary Feeding (PMT) which is carried out during posyandu activities. However, the funds provided by the government are very limited, so cadres have difficulty in managing the PMT budget with a varied menu. This study aims to optimize  the  PMT menu budget using the simplex method so that all toddlers who participate in posyandu activities get a varied PMT by meeting appropriate nutritional needs. This type of research is a case study where the data collection process is through literature studies, interviews with posyandu cadres, and documentation. The menu chosen is corn porridge and roasted brains, because both have the same main ingredient (tilapia) and have nutritional content that is suitable for toddlers. Based on the results of the calculation of the simplex method, it is known that  the budget for corn porridge is IDR 3,000 and grilled brains 2,500 with a capital of IDR 1,320,000. The results of this study show that the application of the simplex method can help cadres in managing  PMT budgets efficiently, but cadres need to pay attention to the nutritional content needed.